Environmental consequences and health risks caused by the pesticide Paraquat in Costa Rica - Montero Rojas, Margoth (2018)
The use of the paraquat pesticide has been widely used around the world and Costa Rica has not been the exception due to its success to treat weeds and their easy availability in the market; with the drawback of being toxic to the environment and human. The objective of this bibliographic review is to unify the existing knowledge of paraquat focused on Costa Rica in order to expose some of the consequences caused by the pesticide. The methodology used was the collection of information through tools such as databases, internet and e-mail. The investigation concluded that it is necessary to reinforce the information used by people who manipulate paraquat to avoid poisoning, in addition to highlighting the need to improve regulations and compliance with the decrees established in our country regarding pesticides.